(untitled) (Scientific journal of the Fergana State University, 2025)
The article provides a general description of the weevil family, the characteristics of the subfamily, as well as the morphological, biological and ecological characteristics of its widespread representatives. Scientific sources are provided about the body coloration and unique wing structure of vizildak beetles. The role of the Carabidae family in metabolism in nature, its grouping by food spectrum, level of vital activity and ecological characteristics has been revealed.